Pengujian Black Box pada Sistem Informasi Barang Berbasis Web Menggunakan Metode Boundary Value Analysis - Bayu Ari Maulana; Ega Mawarni; Moh. Yusuf Hidayattuloh; Vikki Suryawijaya; Aries Saifudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Rayyan Medical is a committed distributor in the field of medical devices together with many hospitals, health departments, health centers and other institutions related to medical devices. However, there are a number of things that need to be considered, especially in the warehouse department, because errors often occur between the data and the available stock. Manual execution produces inconsistent data. So it requires a system that makes it easy to run the process so it doesn't crash all the time. Warehouse requests and requests processing Warehouses still use mail, file storage, and data convenience is less reliable because data storage is unprofitable. From the results of research in , we designed a warehouse inventory system application using the Boundary Value technique. Boundary value testing is testing by dividing the input domains of a program into data groups and then testing only on the input domain boundaries. The aim is to concentrate testing efforts on error-prone areas in accurately setting conditional constraints (for example, the programmer can specify >, if the conditional state is > or =) . Boundary Value Analysis is a widely used Black Box Testing technique, which is also the basis for equivalence testing. This technique tests software with test cases with extreme values of the test data. Boundary Value Analysis is used to identify deficiencies or errors that arise due to limited data input. This technique determines whether a certain range of values is acceptable to the system or not. It is very useful in reducing the number of test cases and is best suited for systems where inputs fall within a certain range.